Kebersihan Diri dalam Hadis: Etika Personal dalam Perspektif Kesehatan Masyarakat - Dinata, Bella; Sulhayani , Sulhayani; Silalahi, Jonson (Arba: Jurnal Studi Keislaman, 2025)
Personal hygiene and maintaining body odor are integral to Islamic teachings, emphasizing both individual and social dimensions. In the modern context, public health issues such as skin diseases, infectious diseases, and decreased social well-being due to poor hygiene further emphasize the urgency of religious studies relevant to public health. Studies of hadith on hygiene have been largely understood within the framework of ritual worship, but have not been widely explored as a basis for public health ethics. This study aims to analyze the Prophet’s hadiths on maintaining bodily hygiene practices—such as bathing, using perfume, grooming hair, and controlling food odors—and examine their relevance to modern health promotion strategies. This study employed a qualitative method with a thematic analysis approach, linking the findings descriptively and analytically to contemporary scientific evidence. The results show that the Prophet emphasized hygiene practices, including regular bathing, using perfume, maintaining personal hygiene, and avoiding the consumption of strong-smelling foods before entering public spaces. These findings align with modern scientific evidence demonstrating that bodily hygiene is effective in reducing bacteria that cause body odor, preventing skin diseases, and increasing social well-being. In addition to the hygienic dimension, these hadiths also emphasize the close relationship between physical cleanliness and spiritual purity, enriching the perspective of health with spiritual nuances. The study’s conclusions confirm that cleanliness in the hadith is not merely individual guidance but also contributes significantly to collective health. This research offers practical implications in the form of strengthening hadith-based hygiene literacy in Islamic public health promotion strategies.